Adverse drug reactions to tocolytic treatment for preterm labour: prospective cohort study. (5th March 2009) - de Heus, Roel; Mol, Ben Willem; Erwich, Jan-Jaap H M; van Geijn, Herman P; Gyselaers, Wilfried J; Hanssens, Myriam; Härmark, Linda; van Holsbeke, Caroline D; Duvekot, Johannes J; Schobben, Fred F A M; Wolf, Hans; Visser, Gerard H A
Abstract : Objective To evaluate the incidence of serious maternal complications after the use of various tocolytic drugs for the treatment of preterm labour in routine clinical situations. Design Prospective cohort study. Setting 28 hospitals in the Netherlands and Belgium. Participants 1920 consecutive women treated with tocolytics for threatened preterm labour. Main outcome measures Maternal adverse events (those suspected of being causally related to treatment were considered adverse drug reactions) leading to cessation of treatment. Results An independent panel evaluated the recorded adverse events, without knowledge of the type of tocolytic used. Of the 1920 women treated with tocolytics, 1327 received a single course of treatment (69.1%), 282 sequential courses (14.7%), and 311 combined courses (16.2%). Adverse drug reactions were categorised as serious or mild in 14 cases each. The overall incidence of serious adverse drug reaction was 0.7%. Compared with atosiban, the relative risk of an adverse drug reaction for single treatment with a β adrenoceptor agonist was 22.0 (95% confidence interval 3.6 to 138.0) and for single treatment with a calcium antagonist was 12 (1.9 to 69). Multiple drug tocolysis led to five serious adverse drug reactions (1.6%). Multiple gestation, preterm rupture of membranes, and comorbidity were not independent risk factors for adverse drug reactions. Conclusions The use of β adrenoceptor agonists or multiple tocolytics for preventing preterm birth is associated with a high incidence of serious adverse drug reactions. Indometacin and atosiban were the only drugs not associated with serious adverse drug reactions. A direct comparison of the effectiveness of nifedipine and atosiban in postponing preterm delivery is needed.